A Survey on Essentials of Machine Learning Algorithms with Python and R codes (International Journal of Advanced Research in Science, Management and Technology, 2021)
Machine learning is a core sub-area of artificial intelligence as it enables computers to get into a mode of self-learning without being explicitly programmed. When exposed to new data, computer programs, are enabled to learn, grow, change, and develop by themselves. We are probably living in the most defining period of human history. The period when computing moved from large mainframes to PCs to cloud. What makes this period exciting for someone is the democratization of the tools and techniques, which followed the boost in computing. Today, as a data scientist, people can build data crunching machines with complex algorithms for a few dollors per hour.
Keywords: Python, Machine Learning, Programming with R, Decision tree, etc